Efficacy and safety of elbasvir/grazoprevir for Japanese patients with genotype 1b chronic hepatitis C complicated by chronic kidney disease, including those undergoing hemodialysis: A post hoc analysis of a multicenter study. Issue 2 (14th September 2018) - Atsukawa, Masanori; Tsubota, Akihito; Toyoda, Hidenori; Takaguchi, Koichi; Kondo, Chisa; Okubo, Tomomi; Hiraoka, Atsushi; Michitaka, Kojiro; Fujioka, Shinichi; Uojima, Haruki; Watanabe, Tsunamasa; Ikeda, Hiroki; et al.
Abstract: Background and Aim: This study aimed to evaluate the efficacy and safety of elbasvir/grazoprevir in genotype 1b chronic hepatitis C Japanese patients with chronic kidney disease (CKD), including those undergoing hemodialysis. Methods: This post hoc analysis of a multicenter, retrospective study included patients who had received elbasvir/grazoprevir. CKD was defined by an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m 2 . The sustained virologic response (SVR) rate and frequency of treatment‐emergent adverse events were assessed in patients with CKD. Results: The study population comprised 155 men and 182 women. The median eGFR level at baseline was 69.6 mL/min/1.73 m 2 (range, 3.0–128.5 mL/min/1.73 m 2 ). Among the 337 patients, 109 (32.3%) had CKD: 72, 14, and 23 (including 20 hemodialysis) had CKD stages 3, 4, and 5, respectively. The SVR rates according to the baseline CKD stages were 98.1% (51/52) in stage 1, 98.3% (173/176) in stage 2, 93.9% (46/49) in stage 3a, 100% (23/23) in stage 3b, 100% (14/14) in stage 4, and 100% (23/23) in stage 5. All 20 patients undergoing hemodialysis achieved SVR. There was no significant decrease from baseline in the median eGFR level throughout the treatment period among the patients with CKD. The incidence of treatment‐emergent adverse events was 6.4% (7/109) among the patients with CKD and 9.7% (22/228) among the patients without CKD (not significant, P = 0.323). Conclusions: The present study demonstrated that elbasvir and grazoprevir are highly effective and safe for genotype 1b chronic hepatitis C Japanese patients with CKD, including those undergoing hemodialysis.